2019
DOI: 10.1111/lam.13236
|View full text |Cite
|
Sign up to set email alerts
|

A case of ‘blown pack’ spoilage of vacuum‐packaged pork likely associated with Clostridium estertheticum in Canada

Abstract: This study investigated the potential causative agents for vacuum‐packaged pork that had shown gross package extension during a routine storage life study in a Canadian pork plant using both conventional and culture‐independent methods. The spoilage‐associated bacteria in purge samples from two packages were enumerated using selective media and profiled using 16S rDNA amplicon analysis. The presence of Clostridium estertheticum was detected using species‐specific real‐time PCR. An enrichment procedure was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…CEC includes diverse psychrophilic and anaerobic species that are commonly isolated from the meat processing environment, and are collectively recognized as a major cause of meat spoilage in chilled and vacuum-packed meat with C. estertheticum being regarded as the most important among the named CEC species ( Wambui and Stephan, 2019 ). Previously, C. estertheticum has been reported to cause BPS in a diverse range of meat including lamb, beef and pork ( Collins, 1992 ; Byrne et al, 2009 ; Zhang et al, 2020 ) but for the first time, we have shown here that it can also cause spoilage in horse meat ( Figure 1C ). Interestingly, we noted that C. estertheticum CM032, which caused BPS in beef, and CM033 and CM034, which caused BPS in horse meat samples, were clonal ( Supplementary Figure 3 ).…”
Section: Discussionsupporting
confidence: 47%
“…CEC includes diverse psychrophilic and anaerobic species that are commonly isolated from the meat processing environment, and are collectively recognized as a major cause of meat spoilage in chilled and vacuum-packed meat with C. estertheticum being regarded as the most important among the named CEC species ( Wambui and Stephan, 2019 ). Previously, C. estertheticum has been reported to cause BPS in a diverse range of meat including lamb, beef and pork ( Collins, 1992 ; Byrne et al, 2009 ; Zhang et al, 2020 ) but for the first time, we have shown here that it can also cause spoilage in horse meat ( Figure 1C ). Interestingly, we noted that C. estertheticum CM032, which caused BPS in beef, and CM033 and CM034, which caused BPS in horse meat samples, were clonal ( Supplementary Figure 3 ).…”
Section: Discussionsupporting
confidence: 47%
“…The samples with the highest spoilage scores were predominated by Clostridium, likely the species C. algidicarnis. In recent years, spoilage of vacuum-packed fresh meat, including beef, lamb, venison, and pork by psychrotrophic clostridia has been reported (40)(41)(42), and the spoilage is typically associated with copious amount of gas production, with C. estertheticum and, to some extent, C. gasigenes being the primary causative agents. C. algidicarnis has been associated with deep tissue spoilage of beef and lamb (43,44) and spoilage of vacuum-packed cooked pork (45).…”
Section: Discussionmentioning
confidence: 99%
“…The genome sequences of the seven meat spoilage Clostridium strains [five strains previously isolated from New Zealand vacuum packed venison and lamb (FP1, FP2, FP3, FP4, M14) and two strains (C. estertheticum DSM 14864 T and DSM 8809 T ) from spoiled beef] were compared with the genome sequences of 33 other strains from the genus Clostridium previously sequenced by other institutes (Table S1, available in the online version of this article) [32][33][34][35][36][37]. All these genomes were re-annotated using Prokka v.1.13.3 [38].…”
Section: Genome Sequencesmentioning
confidence: 99%